Preliminary studies on in vitro sensitivity of Venturia inaequalis populations to some fungicide active ingredients - Fazekas, Mónika; Abonyi, Ferenc; Balla, Barbara; Lakatos, Péter; Holb, Imre (Acta Agraria Debreceniensis, 2012)
Aim of this study was to investigate the sensitivity of conidia of Spilocaea pomi to main fungicide active ingredients (cyprodinil, pirimethanil, fluquinconazole, tebuconazole, difenoconazole, dodine és trifloxistrobin) at dosages of 0.5, 1 and 2 times incubated in vitro at 24 and 48 hours collected from three integrated apple orchards. Results showed that degree of conidial germinations at the fungicide treatnemts decreased in the order of dosages of untreated, 0.5, 1 and 2 times. Considerable conidial germination was observed at higher dosages of some fungicides (e.g. groups of strobilurines and EBI) which confirmed the possibilities of sensitivity reduction of Spilocaea pomi to some funigicides in the sampled Hungarian apple orchards.